2016
DOI: 10.3390/ijms17111839
|View full text |Cite
|
Sign up to set email alerts
|

Tapirira guianensis Aubl. Extracts Inhibit Proliferation and Migration of Oral Cancer Cells Lines

Abstract: Cancer of the head and neck is a group of upper aerodigestive tract neoplasms in which aggressive treatments may cause harmful side effects to the patient. In the last decade, investigations on natural compounds have been particularly successful in the field of anticancer drug research. Our aim is to evaluate the antitumor effect of Tapirira guianensis Aubl. extracts on a panel of head and neck squamous cell carcinoma (HNSCC) cell lines. Analysis of secondary metabolites classes in fractions of T. guianensis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…guianensis, due do its polyphenol content, has been suspected to be involved in different biological properties. Anti-tumoral activities have been underlined in leaf extracts and we found to involve flavonoids (flavonols), tannins, and coumarins [10][11][12]. In rats, methanol extract (ethyl acetate fraction) from leaves of T. guianensis induced vasodilatory and myeloperoxidase-inhibitory were also pointed out in rats, it was determined that hydrolysable tannins (1,4,6-tri-O-galloyl-D-glucose, galloyl-HHDP-hexoside) and flavonoids (myricetin 3-O-α-L-rhamnopyranoside (myricitrin); quercetin 3-O-(6 -O-galloyl)-β-D-galactopyranoside; quercetin 3-O-α-L-arabinofuranoside (avicularin); and quercetin 3-O-α-L-rhamnopyranoside (quercitrin) and quercetin) were involved [13,14].…”
Section: Introductionmentioning
confidence: 80%
“…guianensis, due do its polyphenol content, has been suspected to be involved in different biological properties. Anti-tumoral activities have been underlined in leaf extracts and we found to involve flavonoids (flavonols), tannins, and coumarins [10][11][12]. In rats, methanol extract (ethyl acetate fraction) from leaves of T. guianensis induced vasodilatory and myeloperoxidase-inhibitory were also pointed out in rats, it was determined that hydrolysable tannins (1,4,6-tri-O-galloyl-D-glucose, galloyl-HHDP-hexoside) and flavonoids (myricetin 3-O-α-L-rhamnopyranoside (myricitrin); quercetin 3-O-(6 -O-galloyl)-β-D-galactopyranoside; quercetin 3-O-α-L-arabinofuranoside (avicularin); and quercetin 3-O-α-L-rhamnopyranoside (quercitrin) and quercetin) were involved [13,14].…”
Section: Introductionmentioning
confidence: 80%
“…The present study observed the poorest in vitro inhibitory activity for the B. a ungulata, A. fraxinifolium , S. guianensis, B. variegata candida, and X. aromatica crude leaf extracts toward the glioma cell lines. Therefore, although we have not observed cytotoxic effects for these crude extracts in gliomas, many may have action on other tumor types [ 57 , 58 , 59 , 60 , 61 , 62 ]. Recent studies published by our group revealed the importance of the diversity of secondary compounds in different crude extracts and their selective antitumor potential.…”
Section: Discussionmentioning
confidence: 72%
“…Generally, the major components identified in Annonaceae are, typically, acetogenins [ 64 ], which exhibited in vitro anticancer activities [ 65 , 66 ], which could explain the anticancer activity observed for A. crassiflora , and other Annonaceae like X. aromatica . We also reported the cytotoxic potential of Tapirira guianensis Aubl extracts on a panel of head and neck squamous cell carcinoma cell lines [ 60 ]. In addition, we have previously demonstrated potential antimetastatic activity for B. ungulata extract fractions [ 58 ] and have described the mechanism of action of B. variegata candida fraction on cell viability and inhibitory activity against metalloproteinases in human cervical carcinoma (HeLa) and human peripheral blood mononuclear cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were obtained as previously described by our group (Silva- Oliveira et al, 2016). Briefly, X. aromatica leaves were washed, cut and dried for 5 days at room temperature.…”
Section: Xahf Extractionmentioning
confidence: 99%